Virgo-Death: from The Little Show-Booth by Alexander Blok to The Mistress of Death and The Lover of Death by Boris Akunin - Fedunina, Olga (Literatūra, 2021)
The image of Death, embodied in the image of a beautiful maiden, is considered in the article through the analysis of references in the novel diptych by B. Akunin The Mistress of Death and The Lover of Death (the Erast Fandorin series) to one of the most important primary sources, the drama by A. Blok The Little Show-Booth. The study shows that Akunin’s method of deformation was replaced by a postmodern deconstruction with a splitting into two images, of Columbine and of Maiden-Death, each of which is dominated by one of the hypostases of the heroine of The Little Show-Booth. These transformations appeal in their development to the opposition in Akunin’s novels of two points of view on fate, dialectically interacting, which correlate with the adventurous exposition and with the inevitability of personal destiny idea, oriented towards the “classical” tradition. The result of the analysis is a new formula of the genre of Akunin’s novels, since their poetics goes out of the ordinary framework of criminal literature, as a transgressive phenomenon in the field of mass literature, as postmodern novel, in which the uncertain intertextuality accentuates, align with plot details, the problem of heroes’ self-identity.